Copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction and preparation method and application of copper-based phosphomolybdic acid nanocluster electrode material

By growing copper-based phosphomolybdic acid nanoclusters on a copper foam substrate in situ, the problems of high cost and poor stability of precious metal catalysts have been solved, achieving efficient and low-cost nitrate reduction and ammonia synthesis, and promoting the application of electrocatalysis technology in the field of water treatment.

CN121250409APending Publication Date: 2026-01-02SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511444793.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-10
Publication Date
2026-01-02

AI Technical Summary

Technical Problem

In existing technologies, precious metal catalysts are expensive, scarce, and have poor stability, which limits the application of electrocatalytic reduction of nitrate technology in the field of water treatment. Furthermore, physical and biological methods suffer from high post-treatment costs, complex processes, or poor performance.

Method used

A copper-based phosphomolybdic acid nanocluster electrode material was grown in situ on a copper foam substrate using a one-step solvothermal method. The uniformly distributed nanoclusters provide more adsorption active sites for nitrate reduction reactions.

Benefits of technology

The prepared copper-based phosphomolybdic acid nanocluster electrode material exhibits high conductivity and catalytic activity, demonstrating excellent nitrate reduction performance. Furthermore, the preparation method is simple, reproducible, and inexpensive, making it suitable for large-scale production and enabling the conversion of pollutant nitrate into resource ammonia.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121250409A_ABST
    Figure CN121250409A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction. The preparation method comprises the following steps: (1) dissolving Na2MoO4 2H2O in purified water, and adding concentrated hydrochloric acid and concentrated phosphoric acid; refluxing the mixed solution in an oil bath, adding an NH4CI precipitant, carrying out reduced pressure filtration and air drying to obtain a yellow powdery crude product, dissolving the crude product in purified water at 70 DEG C, slowly evaporating the solution at room temperature, and carrying out reduced pressure filtration to obtain a (NH4) 6P2Mo18O82. 14.2 H2O crystal product; and (2) dissolving the (NH4) 6P2Mo18O62. 14.2 H2O crystal product in deionized water, stirring, transferring into a polytetrafluoroethylene reaction kettle, immersing the treated foamy copper into a solvent, cooling to room temperature, taking out, washing with deionized water and absolute ethyl alcohol, and drying in a vacuum drying oven to obtain the copper-based phosphomolybdic acid nanocluster electrode material. According to the method, in-situ growth of the copper-based phosphomolybdic acid nanocluster on the foamy copper is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrocatalytic materials technology, specifically relating to a copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction, its preparation method, and its application. Background Technology

[0002] Currently, methods for treating nitrate pollution in water bodies can be categorized into physical methods, biological methods, and chemical reduction methods. Physical methods mainly include reverse osmosis, ion exchange, ammonia stripping, and electrodialysis. Ion exchange (IE) utilizes the exchange of ions in an ion exchange resin with nitrate anions flowing through its solution, thereby removing nitrate. Electrodialysis (ED) uses an ion exchange membrane to separate ions from the original solution under the influence of an applied direct current. Reverse osmosis (RO) uses a specific semi-permeable membrane to remove nitrate anions and other ions by forcing water through it. Air stripping adjusts the pH of wastewater to alkaline, converting ionic ammonia nitrogen into molecular ammonia nitrogen, and then uses bubbling to strip the ammonia nitrogen from the wastewater, achieving the goal of removing ammonia nitrogen from the water. These physical methods, such as RO and ED, leave high concentrations of concentrated nitrate residues on the surface of the adsorbent after the reaction and in the reverse osmosis wastewater, requiring secondary treatment. Similarly, air stripping not only requires a large amount of alkali and electricity, but also requires the recovery of ammonia nitrogen in the gas phase to prevent secondary pollution.

[0003] However, these physical technologies suffer from significant drawbacks, such as high post-treatment costs, stringent operating conditions, or cumbersome processes, which are the main factors limiting their widespread application. Biological methods primarily utilize the metabolic processes of denitrifying microorganisms to reduce and remove nitrates. Biological denitrification technologies mainly include: pre-anoxic-aerobic biological denitrification processes, post-anoxic-aerobic biological denitrification processes, simultaneous nitrification-denitrification processes, and short-cut nitrification. Biological methods can convert nitrates in water into nitrogen gas, and are characterized by fewer byproducts and mature technology. Although widely used in practice, they are less effective at removing low concentrations of nitrates, and suffer from high investment and operating costs, complex processes, long treatment cycles, and susceptibility to environmental temperature, water pH, dissolved oxygen, and nutrients.

[0004] Currently used metal catalysts are mostly noble metals such as palladium (Pd), platinum (Pt), ruthenium (Ru), iridium (Ir), and rhodium (Rh). Palladium and platinum are often used for nitrate reduction due to their excellent hydrogen adsorption capacity. However, noble metal materials are expensive and scarce. In addition, the catalytic performance of noble metals is significantly affected by pH. For example, Pt reacts with NO3 under alkaline conditions. -While exhibiting high reduction activity, noble metal nanoparticles are easily dominated by HER in acidic environments. During long-term electrochemical operation, these nanoparticles may aggregate, oxidize, or dissolve (especially under acidic conditions), reducing their stability. These issues severely restrict the widespread application and large-scale promotion of electrocatalysis technology in water treatment. Therefore, exploring efficient, stable, low-cost, and easily prepared alternative electrode materials has become a key direction for overcoming technological application bottlenecks and promoting the practical implementation of electrocatalytic nitrate reduction technology. Summary of the Invention

[0005] In order to overcome the problems existing in the prior art, the present invention aims to provide a copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction, its preparation method and application. The preparation method is simple and readily available, requires no additives, and can realize the in-situ growth of copper-based phosphomolybdic acid nanoclusters on copper foam.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction includes the following steps; Step (1): Dissolve Na2MoO42H2O in pure water, and slowly add concentrated hydrochloric acid and concentrated phosphoric acid while stirring; reflux the mixture in an oil bath, cool to room temperature, and add NH4Cl precipitant to precipitate a large amount of yellow precipitate. Filter under reduced pressure and air dry to obtain a yellow powdery crude product. Dissolve the crude product in pure water at 70 °C, and slowly evaporate the solution at room temperature to precipitate a large amount of yellow-green blocky crystals. Filter under reduced pressure to obtain (NH4)6P2Mo 18 O 82· 14.2H2O crystal product.

[0007] Step (2): (NH4)6P2Mo 18 O 62· 14.2H2O was dissolved in deionized water, stirred, and then transferred to a polytetrafluoroethylene reactor. The treated copper foam was then immersed in the solvent to ensure uniform growth on the material surface. After the temperature was lowered to room temperature, the material was removed, rinsed with deionized water and anhydrous ethanol, and then dried in a vacuum drying oven to obtain copper-based phosphomolybdic acid nanoclusters electrode material.

[0008] In step (1), the ratio of Na2MoO42H2O, concentrated hydrochloric acid, concentrated phosphoric acid, and NH4Cl precipitant is 1:0.8:0.15:1.

[0009] In step (1), 11.12 g of Na2MoO42H2O was dissolved in 50 mL of purified water, and 8.9 mL of concentrated hydrochloric acid and 1.7 mL of concentrated phosphoric acid were slowly added with stirring. The mixture was refluxed in an oil bath for 4 h, cooled to room temperature, and then 11.12 g of NH4Cl precipitant was added, resulting in a large amount of yellow precipitate. The precipitate was filtered under reduced pressure and air-dried to obtain a yellow powdery crude product. The crude product was dissolved in 14.8 mL of purified water at 70 °C, and the solution was slowly evaporated at room temperature. After 3 days, a large amount of yellow-green blocky crystals precipitated. The precipitate was obtained by filtration under reduced pressure to obtain (NH4)6P2Mo 18 O 82· 5.67 g of 14.2H2O crystal product.

[0010] In step (2), the 0.1 mmol (NH4)6P2Mo obtained in step (1) is... 18 O 62· 14.2H₂O was dissolved in 15 mL of deionized water and stirred for 30 min. The solution was then transferred to a 25 mL polytetrafluoroethylene (PTFE) reactor. A 2.5 cm long and 1 cm wide piece of treated copper foam was immersed in the solvent at a 45° angle to ensure uniform surface growth. The solution was maintained at 180°C for 12 h. After cooling to room temperature, the material was removed and rinsed three times with deionized water and anhydrous ethanol. After thorough rinsing, the material was dried in a 60°C vacuum oven for 4 h. The resulting electrode material was copper-based phosphomolybdic acid nanoclusters.

[0011] In step (2), the foamed copper is pretreated foamed copper. The pretreatment step specifically involves washing the foamed copper with acetone, anhydrous ethanol and ultrapure water in sequence.

[0012] A copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction exhibits a microstructure characterized by irregularly distributed 20-50 nm nanoclusters uniformly distributed on its surface. These uniformly dispersed nanoclusters provide more adsorption active sites, demonstrating excellent catalytic activity.

[0013] Application of copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction in electrocatalytic nitrate reduction reaction, wherein the copper-based phosphomolybdic acid nanocluster electrode material serves as the working electrode and the electrolyte includes a solution containing nitrate ions; The electrocatalytic system used is a three-electrode system; the copper-based phosphomolybdic acid nanocluster electrode material is the working electrode, the Ag / AgCl electrode is the reference electrode, and the platinum sheet is the counter electrode.

[0014] The nitrate-containing solution is a sodium sulfate or potassium nitrate solution.

[0015] The electrolyte is a mixture of sodium sulfate and potassium nitrate, with a sodium sulfate concentration of 0.1 mol / L and a potassium nitrate concentration of 50 mg / L.

[0016] The beneficial effects of this invention are: (1) The copper-based phosphomolybdic acid nanoclusters electrode material prepared by the method of this invention exhibits higher electrical conductivity, superior catalytic activity and surface adsorption characteristics, and good conductivity and active area. Specifically, this invention uses a one-step solvothermal method to grow uniformly distributed copper-based phosphomolybdic acid nanoclusters on a three-dimensional copper foam substrate. Immersing the copper foam in the solution at 45°C ensures uniform material growth. After reacting at 180°C for 12 hours, the copper-based phosphomolybdic acid nanoclusters electrode material was successfully prepared. Experimental results show that the electrode material has good conductivity and a large electrochemical active area, and exhibits high electrochemical reduction activity for the electrocatalytic reduction of nitrate. It demonstrates excellent ammonia yield in the electrocatalytic ammonia production process of nitrate, and both the ammonia yield and nitrate removal rate remain stable in the electrode stability test.

[0017] (2) The preparation method provided by the present invention is simple and easy to repeat. The raw materials and conductive substrates used have been mass-produced, are widely available, and have low cost.

[0018] In summary, the copper-based phosphomolybdic acid nanocluster electrode material prepared in this invention exhibits significant technical advantages. Its preparation process is characterized by its simplicity, low cost, and broad applicability, and the resulting material demonstrates excellent structural stability. Under renewable energy power supply conditions, this electrode material can achieve the directional conversion of pollutant nitrate into ammonia, an important chemical raw material, thus constructing an innovative ammonia production strategy that synergistically integrates pollution control and resource recovery. Performance tests show that the copper-based phosphomolybdic acid nanocluster electrode material not only possesses highly efficient electrocatalytic nitrate reduction activity and ammonia synthesis capability but also maintains good stability during long-term reactions, providing a new paradigm for the integration of nitrate pollution control and green ammonia synthesis technologies. Attached Figure Description

[0019] Figure 1 This is a SEM image of the copper-based phosphomolybdic acid nanocluster electrode material in Example 1 of the present invention.

[0020] Figure 2 This is the Cu2p X-ray photoelectron spectrum of the copper-based phosphomolybdic acid nanocluster electrode material in Example 1 of the present invention.

[0021] Figure 3 The image shows the Mo3d X-ray photoelectron spectrum of the copper-based phosphomolybdic acid nanocluster electrode material in Example 1 of this invention.

[0022] Figure 4 The graphs are linear sweep voltammetry (LSV) curves of the electrode materials in Embodiment 1, Comparative Example 1, and Comparative Example 2 of this invention.

[0023] Figure 5The graph shows the ammonia yield and Faraday efficiency of the copper-based phosphomolybdic acid nanocluster electrode material in Example 1 of this invention during nitrate reduction at -1.1 to -1.5V vs. Ag / AgCl.

[0024] Figure 6 This is a stability test performance diagram of the copper-based phosphomolybdic acid nanocluster electrode material in Example 1 of the present invention. Detailed Implementation

[0025] The present invention will now be described in further detail with reference to the accompanying drawings.

[0026] Example 1 A method for preparing a copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction includes the following steps: First, 11.12 g of Na₂MoO₄·2H₂O was dissolved in 50 mL of purified water. While stirring, 8.9 mL of concentrated hydrochloric acid and 1.7 mL of concentrated phosphoric acid were slowly added. The mixture was refluxed in an oil bath for 4 h. After cooling to room temperature, 11.12 g of NH₄Cl precipitant was added, resulting in a large amount of yellow precipitate. The precipitate was filtered under reduced pressure and air-dried to obtain a yellow powdery crude product. The crude product was dissolved in 14.8 mL of 70 °C purified water, and the solution was slowly evaporated at room temperature. After 3 days, a large amount of yellow-green blocky crystals precipitated. This was filtered under reduced pressure to obtain (NH₄)₆P₂Mo. 18 O 82· 14.2H2O crystal product 5.67g; Next, take a piece of foam copper electrode that is 2.5cm long and 1cm wide, put it in acetone solution and ultrasonically clean it, then put it in anhydrous ethanol solution and ultrasonically clean it, and finally put it in deionized water and ultrasonically clean it. Finally, 0.1 mmol (NH4)6P2Mo 18 O 62· 14.2H₂O was dissolved in 15 mL of deionized water and stirred for 30 min before being transferred to a 25 mL polytetrafluoroethylene (PTFE) reactor. The treated copper foam was then immersed in the solvent at a certain angle and kept at 180 °C for 12 h. After the temperature dropped to room temperature, it was removed and rinsed three times with deionized water and anhydrous ethanol. After being thoroughly rinsed, it was dried in a vacuum drying oven at 60 °C for 4 h. The resulting electrode material was copper-based phosphomolybdic acid nanoclusters.

[0027] Example 2 A method for preparing a copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction includes the following steps: First, take a piece of foamed copper electrode that is 2.5cm long and 1cm wide, put it in acetone solution and ultrasonically clean it, then put it in anhydrous ethanol solution and ultrasonically clean it, and finally put it in deionized water and ultrasonically clean it. Secondly, 0.1 mmol (NH4)6P2Mo 18 O 62· 14.2H2O was dissolved in 15mL of deionized water, stirred for 20min, and then transferred to a 25mL polytetrafluoroethylene reactor.

[0028] Finally, the treated copper foam was immersed in the solvent at a certain angle and kept at 160℃ for 12 hours. After the temperature dropped to room temperature, it was taken out and rinsed three times with deionized water and anhydrous ethanol. After being thoroughly rinsed, it was placed in a vacuum drying oven at 60℃ and dried for 4 hours. The resulting electrode material was copper-based phosphomolybdic acid nanoclusters.

[0029] Example 3 A method for preparing a copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction includes the following steps: First, take a piece of foamed copper electrode that is 2.5cm long and 1cm wide, put it in acetone solution and ultrasonically clean it, then put it in anhydrous ethanol solution and ultrasonically clean it, and finally put it in deionized water and ultrasonically clean it. Secondly, 0.1 mmol (NH4)6P2Mo 18 O 62· 14.2H2O was dissolved in 15mL of deionized water, stirred for 10min, and then transferred to a 25mL polytetrafluoroethylene reactor.

[0030] Finally, the treated copper foam was immersed in the solvent at a certain angle and kept at 160℃ for 6 hours. After the temperature dropped to room temperature, it was taken out and rinsed three times with deionized water and anhydrous ethanol. After being thoroughly rinsed, it was placed in a vacuum drying oven at 60℃ and dried for 4 hours. The resulting electrode material was copper-based phosphomolybdic acid nanoclusters.

[0031] Comparative Example 1 A method for preparing an electrode material for nitrate reduction includes the following steps: Take a piece of foamed copper electrode, 2.5 cm long and 1 cm wide, immerse it in acetone solution and ultrasonically clean it, then immerse it in anhydrous ethanol solution and ultrasonically clean it, and finally immerse it in deionized water and ultrasonically clean it; add 0.1 mmol H6PMo 12 O 40 xH2O was dissolved in 15 mL of deionized water and stirred for 30 min, then transferred to a 25 mL polytetrafluoroethylene reactor. The treated copper foam was then immersed in the solvent at a certain angle and kept at 180 °C for 12 h. After the temperature dropped to room temperature, it was removed and rinsed three times with deionized water and anhydrous ethanol. After being thoroughly rinsed, it was placed in a vacuum drying oven at 60 °C and dried for 4 h. The resulting electrode material was copper-based phosphomolybdic acid nanoclusters.

[0032] Comparative Example 2 A method for preparing an electrode material for nitrate reduction includes the following steps: Take a piece of foamed copper electrode that is 2.5 cm long and 1 cm wide, put it into an appropriate amount of acetone solution and clean it with ultrasound, then put it into an appropriate amount of anhydrous ethanol solution and clean it with ultrasound, and finally put it into an appropriate amount of deionized water and clean it with ultrasound, so as to obtain an electrode material without nanoclusters.

[0033] Figure 1 This is a SEM image of the copper-based phosphomolybdic acid nanocluster electrode material in Example 1 of the present invention. Figure 1 As can be seen, by characterizing the morphology of the sample prepared in Example 1 using SEM, it was found that the copper-based phosphomolybdic acid electrode material prepared by the method of the present invention exhibits an irregular nanocluster structure of about 20-50 nm and is uniformly distributed.

[0034] X-ray photoelectron spectroscopy analysis of copper-based phosphomolybdic acid nanocluster electrode materials can determine the chemical state of the surface components in the catalyst. Figure 2 The Cu 2p spectrum of the copper-based phosphomolybdic acid nanocluster electrode material is shown. The peak at approximately 932.47 eV is assigned to Cu 2p. 3 / 2 The peak at around 952.36 eV is assigned to Cu2p. 1 / 2 This shows Cu 2+ and Cu + coexist. Figure 3 The image shows the Mo 3d spectrum of the copper-based phosphomolybdic acid nanocluster electrode material, where the characteristic peaks around 233.27 eV and 236.35 eV binding energies belong to Mo, respectively. 6+ Mo 3d 5 / 2 and Mo 3d 3 / 2 The signal was confirmed by XPS energy dispersive spectroscopy, which further confirmed the successful fabrication of the copper-based phosphomolybdic acid nanocluster electrode material.

[0035] The electrode materials prepared in Example 1, Comparative Example 1, and Comparative Example 2 were used as working electrodes, respectively. Then, the cleaned Ag / AgCl electrode and platinum sheet were used as reference and counter electrodes, respectively. A mixture of 0.1M sodium sulfate solution and 50mg / L potassium nitrate solution was used as the electrolyte. Electrochemical performance was tested on a CS2350M dual potentiostat electrochemical workstation.

[0036] Figure 4 Linear sweep voltammetry (LSV) curves (20 mV·s) of the electrode materials in Embodiment 1, Comparative Example 1, and Comparative Example 2 of this invention. -1 (rate), by Figure 4It can be seen that, compared with the electrode materials in Comparative Examples 1 and 2, under the same overpotential, the current density of the copper-based phosphomolybdic acid nanocluster electrode material in the electrolyte obtained by mixing 0.1 mol / L sodium sulfate solution and 50 mg / L potassium nitrate solution is significantly increased, indicating that the copper-based phosphomolybdic acid nanocluster electrode material has high catalytic activity for nitrate reduction.

[0037] The copper-based phosphomolybdic acid nanocluster electrode material prepared in Example 1 was used as the working electrode. A cleaned Ag / AgCl electrode and a platinum sheet were used as the reference and counter electrodes, respectively. A mixture of 0.1 mol / L sodium sulfate solution and 50 mg / L potassium nitrate solution was used as the electrolyte. Electrolysis of the system using the catalyst was performed using a chronoamperometry method, with the voltage set to -1.1 to -1.5 V vs. Ag / AgCl. After electrolysis for 1 hour, the electrolyte was collected. Under different constant potential conditions, the NH4+ content of the sample from Example 1 was tested in solutions containing 0.1 M sodium sulfate solution and 50 mg / L potassium nitrate. + Yield and Faraday efficiency, such as Figure 5 As shown.

[0038] Figure 5 The curve represents the Faraday efficiency of ammonia synthesis, and the bar chart represents NH4+. + Yield, by Figure 5 It is evident that the copper-based phosphomolybdic acid nanocluster electrode material prepared by the method of this invention possesses excellent electrocatalytic performance and superior selectivity in ammonia synthesis.

[0039] The recyclability of the sample from Example 1 was tested at -1.4V vs. Ag / AgCl in an electrolyte containing 0.1 mol / L sodium sulfate solution and 50 mg / L potassium nitrate solution. Figure 6 As shown, after 30 cycles, the catalyst still maintains excellent nitrate reduction ability and high ammonia yield, indicating the stability and cycle applicability of the prepared catalyst, which is conducive to its industrial application and promotion.

[0040] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. It can be applied to various fields suitable for the present invention. Other modifications can be readily made by those skilled in the art. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and examples shown and described herein.

Claims

1. A method for preparing a copper-based phosphomolybdic nanocluster electrode material for nitrate reduction, characterized in that, Comprise the following steps: Step (1): Na2MoO4 2H2O was dissolved in pure water, and concentrated hydrochloric acid and concentrated phosphoric acid were slowly added under stirring; the mixture was refluxed in an oil bath, and after cooling to room temperature, NH4CI precipitant was added to precipitate a large amount of yellow precipitate, which was filtered under reduced pressure and air-dried to obtain a yellow powder of a crude product, which was dissolved in 70 °C pure water, and the solution was slowly evaporated at room temperature to precipitate a large amount of yellow-green block-shaped crystals, which were filtered under reduced pressure to obtain (NH4)6P2Mo 18 O 82· 14.2H2O crystal product; Step (2): (NH4)6P2Mo 18 O 62· 14.2H2O crystal product is dissolved in deionized water, stirred and transferred to a polytetrafluoroethylene reaction kettle, then the treated foamed copper is immersed in the solvent, so that the material surface grows uniformly, the temperature is reduced to room temperature, taken out, washed with deionized water and anhydrous ethanol, completely washed and dried in a vacuum drying oven, to obtain a copper-based phosphomolybdate nanocluster electrode material.

2. The method for preparing a copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction according to claim 1, characterized in that, In the step (1), the ratio of Na2MoO4 2H2O, concentrated hydrochloric acid, concentrated phosphoric acid, NH4CI precipitant is 1:0.8:0.15:

1.

3. The method for preparing a copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction according to claim 1, characterized in that, In step (1), 11.12 g of Na2MoO4 2H2O was dissolved in 50 mL of pure water, 8.9 mL of concentrated hydrochloric acid and 1.7 mL of concentrated phosphoric acid were slowly added under stirring; the mixture was refluxed in an oil bath for 4 h, and after cooling to room temperature, 11.12 g of NH4CI precipitant was added, a large amount of yellow precipitate was precipitated, which was filtered under reduced pressure and air-dried to obtain a yellow powder of crude product, which was dissolved in 14.8 mL of 70 ℃ pure water, and the solution was slowly evaporated at room temperature, a large amount of yellow-green block-shaped crystals was precipitated after 3 days, and (NH4)6P2Mo 18 O 82· 14.2H2O crystal product 5.67 g.

4. The method for preparing a copper-based phosphomolybdic acid nanocluster electrode material for nitrate reduction according to claim 1, characterized in that, The step (2) in, step (1) 0.1 m mol (NH4)6P2Mo 18 O 62· 14.2H2O was dissolved in 15 mL of deionized water, stirred for 30 min, then transferred to a 25 mL polytetrafluoroethylene reaction kettle, then the treated foam copper with a length of 2.5 cm and a width of 1 cm was immersed in the solvent at 45°, so that the material surface grew uniformly, and was kept at 180℃ for 12 h. After the temperature was reduced to room temperature, it was taken out, washed with deionized water and anhydrous ethanol for 3 times, and completely washed clean, then placed in a 60℃ vacuum drying oven for drying for 4 h. The obtained electrode material was copper-based phosphomolybdate nanoclusters.

5. The method for preparing copper-based phosphomolybdate nanocluster electrode material for nitrate reduction according to claim 1, characterized in that, The foamed copper in the step (2) is pretreated foamed copper, and the pretreatment step is specifically washing the foamed copper with acetone, anhydrous ethanol and ultrapure water in sequence.

6. A copper-based phosphomolybdic nanocluster electrode material for nitrate reduction prepared according to the method of any one of claims 1-5, characterized by, The microstructure of the copper-based phosphomolybdic acid nanocluster electrode material exhibits that the material surface is uniformly distributed with irregular nanoclusters of 20-50nm.

7. Use of a copper-based phosphomolybdic nanocluster electrode material for nitrate reduction according to claim 6, characterized in that, The application of the copper-based phosphomolybdic acid nanocluster electrode material in the electrocatalytic nitrate reduction reaction, the copper-based phosphomolybdic acid nanocluster electrode material as a working electrode, and the electrolyte including a solution containing nitrate; The electrocatalytic system adopted is a three-electrode system; and the copper-based phosphomolybdic acid nanocluster electrode material is a working electrode, the Ag / AgCl electrode is a reference electrode, and the platinum sheet is a counter electrode; The solution containing nitrate is a sodium sulfate and potassium nitrate solution; The electrolyte is a mixed solution of sodium sulfate and potassium nitrate, the concentration of sodium sulfate is 0.1mol / L, and the concentration of potassium nitrate is 50mg / L.